Measurement of performance at institutions of higher learning: the balanced scorecard approach - Krishnan, Anbalagan; Chan, Kwok; Jayaprakash, Jeya; Shaikh, Junaid; Md Isa, A. (Inderscience Publishers, 2008)
Organisations have to confront with new developments brought about by the shift of industrial age competition to information age competition. As a result of this, certain assumptions with regard to the running and measurement of organisational performance have become obsolete. Information becomes essential to bring about new capabilities for competitive success. In the information age, it is vital for organisations to attempt to create future value through investments in customers, suppliers, employees, processes, technology and innovation (Kaplan and Norton, 1998a). Therefore, in information age, organisations need to formulate and utilise performance measurement tools that can be used to develop strategies, not only to create value for the current and future customers, but also to enhance current and future capabilities necessary to improve future performance. The tools are not only to be used to control behaviour and to evaluate past performances, but also to articulate and communicate future strategies. In brief, the objectives of this research study are: evaluate performance measurement at institutions of higher learning; assess the level of awareness and knowledge of balanced scorecard as a measure.